Music and Its Familiarity Affection on Audience Decision Making - Khan, Syazwani Mahsal; Hamid, Assoc. Prof. Dr. Norsiah Abdul; Rashid, Dr. Sabrina Mohd (Jurnal The Messenger, 2019)
This article discuss a problem regarding the lack of using familiar music and its effect on audience decision making to buy advertised products or services. This study is to help the experts to maintain young audience focus while selling their products or services more effective using the familiar music in the advertisement content. The utilization method used for this study was in-depth interview, involved with ten informants which covered experts from academicians, advertising practitioners and musicians. It based on snowball sampling, because not all these experts have the knowledge on this issue. The Elaboration Likelihood Model was applied to show the process of decision making. Thematic analysis used to analyze two themes emerged from this study; Repetition of Musical Tone as Remembrance. This study may provide contribution in terms of ideas for music and advertising industry producing familiar catchy musical sound for their purpose.